A companion to gender prehistory - Bolger, Diane, 1954- (Chichester, U. K. : Wiley-Blackwell, 2013)
'An authoritative guide on gender prehistory for researchers, instructors and students in anthropology, archaeology, and gender studies. This book: Provides the most up-to-date, comprehensive coverage of gender archaeology, with an exclusive focus on prehistory ; Offers critical overviews of developments in the archaeology of gender over the last 30 years, as well as assessments of current trends and prospects for future research ; Focuses on recent Third Wave approaches to the study of gender in early human societies, challenging heterosexist biases, and investigating the interfaces between gender and status, age, cognition, social memory, performativity, the body, and sexuality ; Features numerous regional and thematic topics authored by established specialists in the field, with incisive coverage of gender research in prehistoric and protohistoric cultures of Africa, Asia, Europe, the Americas and the Pacific.'-- Publisher's website.
Includes bibliographical references and index.
Keywords: Prehistoric peoples -- Sex differences; Women, Prehistoric; Social archaeology; Sex role